Prevalence of Hypothyroidism Among Pregnant Women - Dr Anekant Jain; Dr Rajeeb Kalita; Dr Anamika Kore; Shrikant Chandrakar (International Journal of Pharma and Bio Sciences, 2024)
Thyroid disease is one of the commonest endocrine disorders affecting women of reproductive age group & hence constitute the commonest endocrine disorder in pregnancy. It has long been seen that maternal thyroid hormone deficiency or excess can further influence the outcome for the mother & fetus at all stages of pregnancy, as well as interfere with fertility & ovulation. Maternal hypothyroidism is the most common disorder of thyroid function in pregnancy & has been associated with fetal loss, miscarriage, preterm delivery, preeclampsia, low birth weight, placental abruption, fetal distress & reduced intellectual function of the offspring. Pregnancy is very delicate & it is necessary to be aware of the many factors that can further prevent a healthy pregnancy. Awareness of such kinds of problems can lead to the prevention of many complications. Thyroid awareness in pregnancy can further prove to be a lifesaver for both mother & child. We assessed the Hospital Prevalence of hypothyroidism among pregnant women who attended antenatal check-ups in obstetric clinics or were admitted to the obstetrics & gynecology department due to some other obstetrics reasons. A cross-sectional study was done on 200 pregnant irrespective of age, parity, or socioeconomic status. Study subjects who are willing to participate in the study & gave written consent. In our study, we observed that the prevalence of thyroid disorders, especially subclinical hypothyroidism (9.69%), overt hypothyroidism (2.55%) & total hypothyroidism (12.3%), was high. So, our study has paved the way for the acceptance of universal thyroid screening in pregnant women, especially in the Indian context.